Faktor-Faktor yang Mempengaruhi Perilaku Remaja ke Posyandu di Wilayah Kerja Puskesmas Muara Bulian - Yunia Lisma; Ruwayda Ruwayda (Universitas Baiturrahim, 2021)
Posyandu is expected to be a place to facilitate youth in understanding adolescent health problems, find alternative solutions to problems, form youth support groups, expand the reach of PKPR Puskesmas, especially for regional youth who have limited access Data shows that Muara Bulian Health Center, one of the Puskesmas in Batang Hari has provided health services to adolescents through PKPR activities. In 2018 the teen pregnancy rate was 24 teenagers (1.4%), in 2019 there were 27 teenagers (1.6%) An increase of 0.2%. In December 2019, two pilots polyandrous were formed in the work area of the Muara Bulian Community Health Center.This research is a descriptive analytic study with cross sectional method. The population in this study were adolescents who came to Posyandu cendana and singkawang which amounted to 75 people,while the number of samples is 43 people. This research uses purposive sampling technique. Data collection is done by questionnaire. The analysis was carried out univariately and bivariately. Results of the study Some respondents had bad behavior (51.2%) visited Posyandu Most respondents had poor knowledge (55.8%), positive attitude (51.2%), and good family support (62.8%), a good source of information (58.1%), most cadres had a good role (53.5%) in providing services in the Posyandu area of Muara Bulian Puskesmas in 2020. There is a meaningful relationship between knowledge and adolescent behavior . There is a significant relationship between attitude and adolescent behavior. There is a significant relationship between distance with adolescent behavior, there is a significant relationship between information sources and adolescent behavior, there is a relationship between the role of officers with adolescent behavior, and there is a significant relationship between family support and adolescent behavior to the Posyandu in the Public Health Service Muara Bulian Work Area